Dynamics in the automotive industry in Germany, Brazil and India – changes triggered by the COVID-19 pandemic - Christina Teipen; Praveen Jha; Bruno De Conti (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
This article compares modes of response to the COVID-19 pandemic in three national automotive sectors. Our analyses of the automotive sector in Germany clearly demonstrate that trade unions were included and their interests considered at the national, industrial, and company level, and in the negotiations on how EU funds were to be used for technological upgrading. In Brazil and India, on the other hand, large parts of the risks were shifted onto the workforce, thereby further weakening their negotiating positions and without making any progress in catching up with the Global North. Thus, we argue that industrial relations, power and competitive advantages, state assets, and policies at the national level remain the key resource for crisis responses.
Keywords: O17; O57; P52; 330; industrial relations; COVID-19; Global South; automotive sector; technological upgrading